Chronic endometritis: the state of the problem examination - Iuliia E Dobrokhotova; Ekaterina I Borovkova; Viktoriia S Skal'naia; Ivan M Borovkov (IP Berlin A.V., 2019)
Chronic endometritis is a clinical morphological syndrome that develops as a result of a self-sustaining pathological process, which is based on a violation of the production of pro-inflammatory cytokines initiated by an infectious factor. The article presents the clinical and etiological classification of endometritis, the pathogenesis of development in terms of involvement of immunocompetent cells, standards for diagnosis and therapy.